Evolutionary history and population genetics of a cyprinid fish (Iberochondrostoma olisiponensis) endangered by introgression from a more abundant relative - Sousa-Santos, Carla (2014)
Abstract The use of molecular techniques has shown that hybridization and introgression have significant impacts in evolution, by means of transfer of genetic variation and formation of hybrid species. In this paper we use mitochondrial and nuclear sequence data to investigate the evolutionary history, levels of genetic diversity and population differentiation of a rare and endangered fish species. Our results suggest that a hybrid origin scenario of Chondrostoma olisiponensis is a likely explanation for the shared genetic and morphological traits with Iberochondrostoma and Achondrostoma ? Pseudochondrostoma. The basal positioning of C. olisiponensis alleles in all loci analyzed indicates that hybridization events occurred before differentiation within each of these groups, most likely during Middle–Late Miocene. Originally described as C. olisiponensis, we suggest that this species should be placed in the genus Iberochondrostoma to avoid confusion with ‘real’ central European Chondrostoma and to (partially) reflect its evolutionary history. Analyses of levels of genetic diversity and patterns of population subdivision show that populations of the rare Iberochondrostoma olisiponensis are differentiated (high and significant uST and FST) and genetically depauperate (very low S, p, and h). I. olisiponensis is simultaneously imperiled by small population sizes and contemporary bidirectional hybridization with another critically endangered sympatric species (Iberochondrostoma lusitanicum). Urgent ex-situ conservation measures involving supportive breeding of I. olisiponensis are needed to preserve present genetic variation and eventually increase in situ population sizes, along with further studies focused on different life history and behavioral characteristics of this highly endangered species.